Segredo, transparência e as perspectivas para a política externa democrática no Brasil - Pinheiro, Ruan Sales de Paula [UNESP] (2015)
The demand for the opening of the centers of power to public scrutiny has been rapidly and globally expanded since the second half of the twentieth century. In Brazil, the term transparency has come to be invoked with remarkable frequency in recent years as a solution to many of the nation’s problems. In 2011, the Access to Information Act (Lei de Acesso à Informação), which regulates the opening of public body to citizens, was approved and in the same year, Brazil became the leader of the international initiative called Open Government Partnership (Parceria para o Governo Aberto - OGP). This is, however, a late advance. While the prescriptive compliance with the principle of publicity only appears in the Constitution of 1988, many enactments, executive orders and laws had addressed to the protection of official secrecy since the Independence of Brazil. With that in mind, this work is dedicated to exploring aspects of the history of the country that allow tracing the genesis and the evolution of the dynamics between secrecy and transparency in Brazil, in order to analyze the limits and possibilities to the opening and democratization of our foreign policy.